Manuscript Rejection in Academic Journals: Some advice to doctorate students - Adel CHIHEB; Mohammed BOUKEZZOULA (Langues & Cultures)
Publishing a research article in a peer-reviewed journal is an essential step in advancing one's career as a researcher. However, the competitive nature of academic publishing coupled with high submission volumes and rejection rates necessitates that authors understand the reasons behind manuscript rejections and adopt the appropriate strategies to improve their publication success. In this article, we discuss the common reasons why articles are rejected and suggest strategies that authors can use to improve their chances of seeing their articles accepted for publication.